Effectivity of Environment-based Learning Method - Suryandari Suryandari (Green Visioneers, 2020)
The quiddity of knowledge is about a collection of knowledge, a process, a collection of values, ​​and one way to get to know the world. Therefore, learning science becomes complex to minimize apperception and understand concepts. One of the lessons that can be done is science learning with an environment-based learning model where the object of learning is oriented to real experiences, collecting data directly, so that the data obtained is accurate. This study provides a picture of the role of environment-based learning in the cognitive and affective domains of students, both from the teacher's and students' perspectives. Based on the results of research studied from science-based learning results in an increase in learning outcomes to student skills such as critical thinking skills, problem-solving to conceptual understanding. The positive role can also be understood by teachers when developing environment-based learning because science learning can be exemplified in real terms and motivate teacher creativity in utilizing the environment both material and material within the school environment. In the affective domain, changing students' attitudes such as motivation and interest in learning, scientific attitudes, and attitudes to care for the environment.